FEATURES OF FOLK TRADITIONS IN THE MORAL EDUCATION OF PRIMARY SCHOOL AGE IN THE FAMILY AND SCHOOL BASED ON FOLK TRADITIONS (Konferensiyalar | Conferences, 2024)
Restore the ancient spiritual and moral aspects of our people; take measures to preserve our cultural wealth, created over the centuries, as a unique talent and pass it on to future generations; always remember and develop ancient and modern folk abilities; defense of spiritual abilities as universal and universal human abilities; implementation of such conditions as achieving in-depth study of the content and essence of national abilities at all levels of the educational system, especially in the education of the younger generation and adolescents.